Policy Making and Information Dissemination in Nigeria: Challenges and the Way Forward - Oji, Okechukwu Richard (SOUTH EAST JOURNAL OF POLITICAL SCIENCE, 2021)
This paper examines the role of Policy Making particularly as it relates to information dissemination in Nigeria. It notes the various ways to policymaking and the various stages and processes to its actualization. The paper further notes roles of the citizen in the formulation of a good policy and the need for their participation in jointly building towards a healthy society through the creation of a peaceful and robust economy aimed at the provision of better living standards in Nigeria. It highlights the challenges to policy making and proffers solutions towards a credible policymaking and Implementation strategy in the creation of a peaceful society in Nigeria.